Application of membrane bioreactors for the purpose of wastewater purification from bioresistic pharmaceutical products - Бойченко, Сергій Валерійович; Бойченко, Марія Сергіїна; Шаманський, Сергій Йосипович (Science-based technologies, 2020)
The article deals with the negative impact of illiquid pharmaceuticals that are not properly utilized on the environment. A significant problem is that about 140,000 tonnes of pharmaceuticals are not used and are converted to waste in the EU countries. About 30% of them are not properly utilized. Despite the fact that EU legislation requires the establishment of a system for collecting and disposing of unused drugs in healthcare facilities, there is no such system at present. One of the main ways for pharmaceuticals to enter surface and groundwater are sewage effluents from pharmaceutical factories, urban sewage, hospital sewage, as well as landfills for solid waste. It is not always possible to determine the concentrations of all pharmaceuticals in the effluent. Therefore, the problem of their removal from wastewater is urgent today. The article presents a comparative analysis of the effectiveness of known methods and technologies for the treatment of wastewater and other waters from pharmaceuticals. It is shown that the existing treatment plants in Ukraine are not adapted for either removal or decomposition of medicines. There is also no regulatory framework governing the discharge of organic micro-pollutants into water bodies. The conclusion is made about the necessity of considering the life cycle of pharmaceuticals. The strategic approach to the environmental impact of the pharmacological industry should determine specific actions at all stages of the life cycle, from research, design and development to final disposal. Recommendations on the use of membrane bioreactors for the removal of pharmaceuticals from wastewater have been formed. A block diagram of a universal two-stage membrane bioreactor is proposed, which is intended for carrying out both biosynthesis processes with the use of producing microorganisms and bioconversion processes with simultaneous purification and concentration of target biologically active substances. The advantages of using such schemes are shown, as well as recommendations on the use of calculation methods for treatment installations.